Desenvolvimento de uma técnica de microamostragem utilizando impregnação de sangue em papel filtro para análise de biomarcadores de zearalenona e deoxinivalenol em suínos - Laber, Isadora Fabris (2025)
Swine farming plays a significant economic role in the animal production chain, maintaining steady growth over several decades. Mycotoxins are fungal metabolites that negatively affect organisms in various harmful ways, interfering with physiological processes and resulting in reproductive damage, oxidative stress, endocrine disorders, cytotoxicity, and immunotoxicity. The toxins zearalenone (ZEA) and deoxynivalenol (DON), produced by fungi of the genus Fusarium spp., have a significant impact on the production chain due to the susceptibility of pigs to these toxins. Unlike conventional evaluations of mycotoxins in feed and ingredients, assessing exposure to mycotoxins through biomarkers can provide an individualized analysis of consumption and enable the in vivo evaluation of the efficacy of anti-mycotoxin additives (AMA). Therefore, this study aimed to develop and validate a methodology for evaluating biomarkers of DON, ZEA, and their metabolites α-zearalanol (α-ZAL), zearalanone (ZAN), deepoxy-deoxynivalenol (DOM-1), and 3-acetyl-DON (3-ADON) in swine blood impregnated on qualitative filter paper. For the development and validation of the method, blood samples were collected in EDTA tubes at the slaughter of three 70-day-old Landrace pigs with no prior exposure to mycotoxins. The blood samples were fortified with 20, 40, and 60 μg/L of a mix containing 1,000 μg/L of DON, ZEA, α-ZAL, ZAN, DOM-1, and 3-ADON. Subsequently, 40 μL of each concentration were impregnated in pre-marked circles on qualitative filter paper, in septuplicate. After drying, the impregnated blood samples were cut, extracted, and quantified using HPLC-MS/MS. The following parameters were evaluated for method validation: limits of detection and quantification, linearity, analytical curve, matrix effect, recovery, and selectivity. The method successfully detected ZEA, α-ZAL, ZAN, DON, DOM-1, and 3-ADON in dried blood spot (DBS) samples. ZEA, α-ZAL, ZAN, and DON met all required parameters for method validation, with average recoveries of 89.10%, 74.66%, 79.79%, and 101.50%, respectively. Thus, the method was validated for the analysis of ZEA, α-ZAL, ZAN, and DON in swine blood, meeting the criteria established by regulatory authorities. Furthermore, qualitative filter paper proved to be an effective alternative to conventional collection papers, making the method more accessible compared to previously developed methods.